2019
DOI: 10.3389/fcell.2019.00152
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Breakdown in T Cells: Role of Membrane Compartmentalization in T Cell Signaling and Interference by a Pathogen

Abstract: Sphingolipids are major components of cellular membranes, and at steady-state level, their metabolic fluxes are tightly controlled. On challenge by external signals, they undergo rapid turnover, which substantially affects the biophysical properties of membrane lipid and protein compartments and, consequently, signaling and morphodynamics. In T cells, external cues translate into formation of membrane microdomains where proximal signaling platforms essential for metabolic reprograming and cytoskeletal reorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 149 publications
(255 reference statements)
0
15
0
Order By: Relevance
“…The impact of sphingolipid metabolism on pancreatic tumor growth and tumor phenotypes is not well described. In the context of membrane lipids, sphingolipids, which reside extensively on the outer leaflet of the membrane, regulate membrane fluidity, which is important for membrane plasticity during vesiculation, as well as endo/exocytosis [ 26 , 27 , 28 ]. In addition, membrane proteins and associated membrane signaling components compartmentalize within membrane domains at steady-state conditions or in response to stimulation or metabolic signals.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sphingolipid metabolism on pancreatic tumor growth and tumor phenotypes is not well described. In the context of membrane lipids, sphingolipids, which reside extensively on the outer leaflet of the membrane, regulate membrane fluidity, which is important for membrane plasticity during vesiculation, as well as endo/exocytosis [ 26 , 27 , 28 ]. In addition, membrane proteins and associated membrane signaling components compartmentalize within membrane domains at steady-state conditions or in response to stimulation or metabolic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on primary human nasal and murine tracheal epithelial cells showed that it triggers lipid microdomain transformation into large platforms of insoluble membranes to stimulate its internalization [ 109 ], the stimulation of CD95 and CD40 trigger membrane reorganization subjecting acid sphingomyelinase (ASM) toward the extracellular leaflet. Thus, leading to the breakdown of sphingomyelin to ceramide [ 110 , 111 ]. This is further required to reorganize these microdomains into larger signaling platforms [ 112 ].…”
Section: Host Lipids and Bacterial Endocytosismentioning
confidence: 99%
“…Several studies have shown that acidic sphingomyelinase and ceramide play an important role in the infection of cells with P. aeruginosa [ 173 ]. It was found that P. aeruginosa can initiate the activation of acidic sphingomyelinase, which hydrolyzes sphingomyelin [ 174 , 175 ] to form ceramide.…”
Section: Cross-links Of Lipid Metabolism and Bacterial Infection In The Lungsmentioning
confidence: 99%